High temporal resolution arterial spin labeling MRI with whole‐brain coverage by combining time‐encoding with Look‐Locker and simultaneous multi‐slice imaging. Issue 6 (3rd March 2019) - van der Plas, Merlijn C.E.; Teeuwisse, Wouter M.; Schmid, Sophie; Chappell, Michael; van Osch, Matthias J.P.
Abstract : Purpose: The goal of this study was to achieve high temporal resolution, multi‐time point pseudo‐continuous arterial spin labeling (pCASL) MRI in a time‐efficient manner, while maintaining whole‐brain coverage. Methods: A Hadamard 8‐matrix was used to dynamically encode the pCASL labeling train, thereby providing the first source of temporal information. The second method for obtaining dynamic arterial spin labeling (ASL) signal consisted of a Look‐Locker (LL) readout of 4 phases that are acquired with a flip‐angle sweep to maintain constant sensitivity over the phases. To obtain whole‐brain coverage in the short LL interval, 4 slices were excited simultaneously by multi‐banded radiofrequency pulses. After subtraction according to the Hadamard scheme, the ASL signal was corrected for the use of the flip‐angle sweep and background suppression pulses. The BASIL toolkit of the Oxford Centre for FMRIB was used to quantify the ASL signal. Results: By combining a time‐encoded pCASL labeling scheme with an LL readout and simultaneous multi‐slice acquisition, 28 time points of 16 slices with a 75‐ or 150‐ms time resolution were acquired in a total scan time of 10 minutes 20 seconds, from which cerebral blood flow (CBF) maps, arterial transit time maps, and arterial blood volume could be determined. Conclusion: Whole‐brain ASL images were acquired with a 75‐ms time resolution for the angiography and 150‐ms resolution for the perfusion phase by combining the proposed techniques. Reducing the total scan time to 1 minute 18 seconds still resulted in reasonable CBF maps, which demonstrates the feasibility of this approach for practical studies on brain hemodynamics.